Longitudinally extensive transverse myelitis after COVID-19 vaccination in a teenage girl - Arun Prasad; Kumar, Pradeep; Banerjee, Amrita; Ghosh, Dipyaman (International Journal of Contemporary Pediatrics, 2023)
COVID-19 pandemic has led to the development of a variety of vaccines for protection against SARS-CoV-2 infection, with varying safety profiles and protective efficacy. As with other vaccination, vaccination against COVID-19 has also been found to be associated with various kinds of adverse events following immunization. While most adverse effects are mild, some serious side effects like transverse myelitis and acute disseminated encephalomyelitis have also been reported. However, these serious side effects have been reported in adults. To the best of our knowledge, there is no report of longitudinally extensive transverse myelitis (LETM) in the paediatric population, associated with this vaccination. We report here a case of a teenage girl, who was admitted to our hospital with the symptoms of LETM after receiving COVID-19 vaccination. Her diagnosis was based on history and, laboratory and imaging findings. She was discharged after a full recovery.